Perforated small bowel reticulosarcoma in free peritoneum - Mazza, Milton E; Sarroca, E; Reisenweber, j (Cirugía del Uruguay, 2020)
Malignant thin lymphomas are less rare tumors than is generally believed. Even if its total frequency is not very high, it is worth noting that it is they are in relation to other tumors of the thin as all the statistics attest ...